Leadership for Instructional Improvement: A Design Research Approach to Integrating Makerspace and Project-Based Learning in Science Classrooms in an Urban Middle School - Claudet, Joseph (Advances in Social Sciences Research Journal, 2021)
Effectively integrating creative experiential learning opportunities into classroom-based science instruction to enhance students’ applied learning continues to be a challenge for many middle school educators. This article explores how educators in one urban middle school leveraged design research thinking in conjunction with collaborative data-teaming processes to develop a targeted professional learning intervention program to help seventh- and eighth-grade teachers learn how to integrate Makerspace hands-on experiential and project-based learning activities into their STEM instructional practices to better engage students in applied science learning in middle school classrooms. A literature-informed discussion is included on how the middle school principal and the school’s instructional improvement team utilized focused professional development activities and intensive Professional Learning Community (PLC) conversations to positively transform teachers’ pedagogical mindsets and instructional practices in support of integrating Makerspace and related project-based experiential learning opportunities as valuable components of classroom-based science teaching and learning. Finally, a number of design principles derived from the middle school case study highlighted in this article are offered that may be of practical use to school leaders interested in applying educational design research methods to enhance their own campus-based instructional improvement efforts.